(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The primary objective of studying bioethics in educational institutions is to provide students with knowledge about technical and technological objects and processes, teach them practical work methods, and develop personal qualities, creative thinking, and the ability to work independently.